The Syllabus Enhancement for Medical Imaging in Biomedical Electronics - Saidatul, A.; Mohamad, N. F.; Mohd Yusof, B.; Fadzly, R. (Thai Medical Physicist Society, 2010)
9th Asia-Oceania Congress of Medical Physics (9th AOCMP)is organized by Thai Medical Physicist Society, 22nd-24th October 2009, The Empress Convention Center, Chiangmai, Thailand.